The Predicament of FinTechs in the Environment of Traditional Banking Sector Regulation~– An Analysis of Regulatory Sandboxes as a Possible Solution - Johannes M. Gerlach; Daniel Rugilo (Credit and Capital Markets – Kredit und Kapital, 2019)
Recently, "Financial Technology-companies" (FinTechs) are increasingly changing the financial services industry worldwide and impose considerable challenges for regulators tasked to solve the arising trade-off between sound regulation and innovation support. In this regard, regulatory sandboxes, which were recently introduced in several jurisdictions, provide a promising solution, as they imply a liberalization of regulatory requirements in order to enable FinTechs to test their innovative services. However, we observe that no comparable initiative exists in Germany, even though the German regulator identified a need for action on this subject in order to maintain its international competitiveness. Thus, based on a detailed analysis of various sandbox models worldwide, this paper develops a set of own recommendations as a basis for the implementation of a sandbox concept which might be applicable in the German regulatory environment. In doing so, we identify current theoretical as well as practical regulatory issues within the context of the rapid FinTech evolution. To the best of our knowledge, this paper represents the first study on key international sandboxes as a basis to design guidelines specifically for the German financial market. Thereby, we contribute to the literature as we evolve an effective regulation within the new setting of innovative financial technologies. Moreover, our findings contribute to the practical solution of current challenges faced by both regulators and affected companies. Even though our derived implications focus on the German financial sector, the results may potentially be applicable in further jurisdictions with similar regulatory requirements.
Keywords: G21; G28; M13; 330; digital finance; FinTech; financial sector; financial regulation; FinTech regulation; financial stability; regulatory sandbox; financial services industry